Multicultural Leadership Principles in Islamic Education: A Quranic and Hadith Perspective - Rahmad Espihani; Tuti Fiani; Jasiah Jasiah; Muslimah Muslimah; Normuslim Normuslim; Dakir Dakir (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This article discusses the normative foundation of multicultural leadership from the perspective of the Qur'an and Hadith, as well as strategies for improving the quality of madrasah learning in the context of implementation and challenges in the era of globalization. Multicultural leadership has become a necessity in heterogeneous educational environments, especially in madrasahs, which not only serve as centers for religious education but also play a strategic role in the formation of national character. The Qur'an and Hadith provide basic principles such as justice, consultation, tolerance, and respect for differences as a foundation for building inclusive leadership. In the context of globalization, madrasahs face challenges such as technological disruption, changes in social values, and global educational quality standards. Therefore, the strategy for improving the quality of learning needs to be directed towards strengthening teacher competencies, developing a curriculum that is responsive to the needs of the times, and visionary and adaptive school leadership in the face of change. This article uses a descriptive qualitative approach with literature study as the main method. The results of the study indicate that the integration of multicultural leadership values based on Islamic teachings and contextual quality improvement strategies are key in addressing the challenges of madrasahs in the era of globalization.